EFEKTIVITAS PENYULUHAN UNTUK MENINGKATKAN PENGETAHUAN KESEHATAN GIGI DAN MULUT SISWA KELAS V SDN 16 KESIMAN DENPASAR TIMUR - Ni nyoman Dewi Supariani; Ni Ketut Ratmini (Jurnal Kesehatan Gigi (Dental Health Journal), 2016)
According to Kwan, et al., (2005) in Sriyono (2009) oral health is a fundamental part of general health and wellbeing. According Riyanti and Erika (2005) in Nuzurabachtiar (2013), dental hygiene and oral health is part of the body that can not be separated from one another, because oral health affects the health of the body. Riskesdas (2013) reported that the prevalence of dental caries in Bali is for 24.0 with the translation of caries prevalence for the age group of 12 years was 22.1% with Decay, Missing, Tooth Filling (DMF-T) 0.55, 35 age group -44 years of dental caries prevalence reached 26.9% with DMF-T 4.56. The problem of this research is "Effective counseling to increase knowledge of fifth grade students of SDN 16 Kesiman Denpasar East 2015". The purpose of this study was to determine the effectiveness of counseling for increasing knowledge of fifth grade students of SDN 16 Kesiman Denpasar Timur in 2015. This study is the research experiment with Paired T test. The population in this study were all students of class V SDN 16 Kesiman Denpasar are 71 East. This study does not use samples but using total population. Based on the results of research conducted on 71 students of class V SD N 16 Kesiman Denpasar Timur obtained results regarding the level of knowledge about dental and oral health care before getting dental health education with very good criteria as many as 18 people (25.35%), the level of knowledge of students with good criterion as many as 37 people (52.11%), the level of knowledge of students with criteria quite as many as 13 people (18.30%), while the level of knowledge of students with less criteria of three people (4.22%) and no student have failed criteria, and the average level of knowledge of students of class V SD N 16 Kesiman about maintaining healthy teeth and mouth before getting dental health education amounted to 72.32, which means knowledge of fifth grade students were on both criteria.The frequency of the level of knowledge of students of class V SD N 16 Kesiman obtained results regarding the level of knowledge about dental and oral health maintenance after getting dental health education with very good criteria as much as 67 people (94.36%), while the level of knowledge of students with good criterion as many as four people (5.63%), and no students have sufficient criteria, less and failed and the average level of knowledge of students of class V SDN 16 Kesiman about maintaining healthy teeth and mouth before getting dental health education amounted to 89.86, which means the knowledge of students V class currently on the criteria very well. The results of the bivariate analysis showed that the correlation test Paired T test showed that the correlation coefficient (R) =, 599 and sig = 0,000. This shows that there is a significant association between knowledge and before and after being given the oral and dental health education in the fifth grade students of SDN 16 Kesiman. Expected for dental health workers in order to improve the knowledge of students of class V SD N 16 Kesiman, by providing information or counseling on dental and oral health maintenance.